If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1m + -13 = -22 Reorder the terms: -13 + -1m = -22 Solving -13 + -1m = -22 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1m = -22 + 13 Combine like terms: -13 + 13 = 0 0 + -1m = -22 + 13 -1m = -22 + 13 Combine like terms: -22 + 13 = -9 -1m = -9 Divide each side by '-1'. m = 9 Simplifying m = 9
| 3y-21=-24 | | 12x-4=3x+13 | | 4x-23=-24 | | y=9x^4-16lnx | | x+6a=21+ax-6a | | -4m+5=-7 | | 9.2x=0 | | 19-2t=11 | | -10x-13=67 | | 3x*(x+5)+(3x+1)*(x-1)=18 | | 3=-12c+6 | | X(3+y)=8 | | 4b-6=-10 | | -9p+18=99 | | 80=90x-120 | | -7b+35=-7(4b-5) | | -21-b=6(2b+3) | | 3x-21=-42 | | 14-5b=-2(1+7b)-2 | | 4x^2+15x-1=18 | | 4(h-12)=44 | | 8p+2=-54 | | -7(n-3)+2n=-4n+26 | | -7m-12=-40 | | -2(x+8)+5=-23+x | | 7m-20=15 | | 7x+35=180 | | 72+6x=11(14x+20) | | 7m-24=-24 | | 72+6x=11(14x+50) | | -6x-19=-1 | | 8/9-4/5 |